Thematic content analysis of literature regarding academic misconduct and the use of technology - Appier, Mark Alan (My University, 2025)
Academic misconduct continues to be an endemic problem in schools. This study uses a broad systematic literature review of one-hundred papers covering 79,821 students to explore the factors causing moral disengagement to occur in order to identify the underlying motivations which are pressuring students into behaviors such as plagiarism and cheating. This study examines the prevalence of these behaviors and evolution through four eras of technology which are labeled “old-school”, “retro-tech”, “high-tech”, and into the fledgling era of “AI”. In doing so, the study investigates student-reported causes of academic dishonesty and rationalizations given as motivations prompting moral disengagement as defined by Bandura, and specific triggers tipping the risk-reward balance in favor of academic dishonesty. Examination of these factors was accomplished through content analysis of a selected body of primary research literature of unique studies, cataloging data from those studies using ethnographic thematic analysis to create comparisons of qualitative, quantitative, and mixed methods studies. It was found, using a subjective inter-study comparison looking at technology, not chronology or geography, that although the concern with some types of academic misconduct increased such as falsification of work and plagiarism increased, the overall prevalence of academic misconduct as well as factors contributing to moral disengagement, decreased with the advancing levels of technology. The implication of these findings is that educators should continue their strategies addressing unintentional and intentional academic misconduct. This study shows a clear relationship between academic misconduct and the technology available. However, more research is needed to establish a more granular baseline by which to evaluate the fledgling technology of artificial intelligence and its effects on academic misconduct.
Keywords: Academic misconduct; Academic dishonesty; Cheating; Moral disengagement; Plagiarism; Unintentional academic misconduct